1999
DOI: 10.1143/jjap.38.147
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Rotation in an Antiferroelectric Liquid Crystal Studied by 13C-Nuclear Magnetic Resonance Spin-Lattice Relaxation Time Measurement

Abstract: Temperature dependence of the spin-lattice relaxation time T 1 was measured in an antiferroelectric liquid crystal, 4-(1-methylheptyloxycarbonyl) phenyl-4′-octyloxybiphenyl-4-carboxylate (MHPOBC) by means of 13C-nuclear magnetic resonance (NMR). The activation energies determined by the temperature dependence of T 1 are the same for most of the carbon nuclei in the SmA and SmCA * phases, whereas they are different for carbon nuclei at the chiral center and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…2), it can be concluded that the relaxation mechanism observed is mainly dominated by the magnetic dipole-dipole relaxation process caused by the overall rotation about the molecular long axis. 22) According to the previous T 1 studies for an antiferroelectric liquid crystal of S-MHPOBC, the correlation time c of molecular rotation is estimated at about 10 À8 s in the SmC A Ã phase, where the T 1 minimum occurs under a condition of ! 0 c $ 1.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…2), it can be concluded that the relaxation mechanism observed is mainly dominated by the magnetic dipole-dipole relaxation process caused by the overall rotation about the molecular long axis. 22) According to the previous T 1 studies for an antiferroelectric liquid crystal of S-MHPOBC, the correlation time c of molecular rotation is estimated at about 10 À8 s in the SmC A Ã phase, where the T 1 minimum occurs under a condition of ! 0 c $ 1.…”
Section: Resultsmentioning
confidence: 98%
“…21) In addition, Tokumaru et al measured the 13 C-NMR spin-lattice relaxation time T 1 , which is dominated by the molecular rotation, and confirmed that the activation energies obtained at carbonyl carbons in the SmC A Ã phase of MHPOBC are higher than those in SmA. 22) Seki and coworkers recently estimated that the correlation time c of the molecular rotational motion should be of the order of 2=! 0 $ 10 À8 s in the SmC A Ã phase, when the spin-lattice relaxation time T 1 of the aromatic core is minimum.…”
Section: Introductionmentioning
confidence: 93%
“…However, it is not straightforward to carry out these in reality. To list a few recent 13 C relaxation works, these include 10B1M7 [217], 4-(1-methylheptyloxycarbonyl)phenyl-4 0 -octyloxybiphenyl-4-carboxylate (MHPOBC) [218][219][220], 4-(2-methyloctanoyl)phenyl 4 0 -nonylbiphenyl-4-carboxylate (MONBIC) [216], 4-(1-methylhexyloxycarbonyl) phenyl 4 0 -octyloxybiphenyl-4-carboxylate (MH(6)POBC) [221]. In general, the 13 C T À1 1 rates of the aromatic carbons increase with decreasing temperature in a manner similar to the observed spectral densities for the aromatic deuterated sites (see for instant, ZLL 7/* [189]).…”
Section: Bent-core and Dendritic Mesogensmentioning
confidence: 99%
“…As for its dynamical aspect, however, details of the hindered molecular rotation associated with the emergence of spontaneous polarization are still open for question, although several experimental approaches have been carried so far [1][2][3][4][5][6][7][8][9][10][11][12][13]. Although nuclear magnetic resonance (NMR) spectroscopy is a powerful method for investigating molecular dynamics in liquid-crystalline compounds, neither the slowing down nor the hindrance of molecular rotation has been confirmed even in recent studies [14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%